Reconstructing the Islamization of Science to Address Critical Issues in Modern Education - Basri Saenong; Muljono Damopolii; Munawir Kamaluddin (CV. Edujavare Publishing, 2026)
The rapid advancement of science and technology has transformed modern education while simultaneously creating critical challenges related to ethical degradation, epistemological dualism, technological disruption, and the declining integration of moral and spiritual values within educational systems. This study aims to reconstruct the Islamization of science as a contemporary educational paradigm capable of addressing these challenges through the integration of revelation, reason, and empirical scientific inquiry. The study employed a qualitative library research design using a conceptual and analytical approach. Data were collected from classical Islamic scholarship, contemporary books, and peer-reviewed journal articles published primarily between 2020 and 2025. The literature was analyzed using qualitative content analysis through data reduction, thematic categorization, interpretation, and synthesis to formulate an integrative framework for the reconstruction of the Islamization of science. The findings indicate that reconstructing the Islamization of science extends beyond philosophical discourse by providing practical implications for curriculum development, pedagogical innovation, digital literacy, ethical scientific research, and institutional leadership. The reconstructed framework promotes a holistic educational model that integrates scientific competence with ethical responsibility, spiritual awareness, environmental stewardship, and social justice. Furthermore, it encourages interdisciplinary collaboration and responsible technological innovation while preserving scientific rigor and academic excellence. The study concludes that the reconstruction of the Islamization of science offers a sustainable educational paradigm capable of producing graduates who are intellectually competent, morally responsible, spiritually grounded, and globally competitive in addressing the increasingly complex challenges of the twenty-first century.